Severe thrombocytopenia soon after drug-eluting stent implantation in ST-elevation myocardial infarction - Łebek-Szatańska, Agnieszka; Pośnik-Kisło, Anna; Błaszak-Ciećwierska, Wiesława; Dąbrowski, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Thrombocytopenia is among the most frequent haematological issues in patients hospitalised with myocardial infarction. We discuss the case of a 77-year-old male who was admitted to hospital on the 4th hour of ST-elevation myocardial infarction of the anterior wall. A percutaneous coronary intervention to critically stenoted initial segment of the anterior descending branch was performed. A few days later he started developing symptomatic thrombocytopenia. On the course of his long hospitalization we faced many important problems, concerning both diagnosis and treatment of these co-existing conditions.